'He didn't really talk about it': the (re)construction and transmission of a Free French past. (2nd October 2021) - Millington, Chris; Millington, Richard
ABSTRACT: This article examines the wartime experience of Hilaire Marteau, a teenage member of Charles de Gaulle's Free French who settled in Liverpool after the war. Marteau's tale has all the ingredients of a Hollywood adventure: courageous resistance, a daring escape from Nazi Germany, and a perilous crossing of the Pyrenees to join the fight against Hitler and Vichy France. That, at least, is the story according to Marteau's rough notebooks and conversations with his relatives, for he died before authoring a planned memoir. This article presents our efforts to reconstruct his story through these writings and through interviews with his surviving family members. It reveals not only how Marteau represented his own past but also the ways in which he passed his story on to his wife and children. In doing so, the article suggests ways in which historians might explore 'second-generation' memory of French resistance.